2018
DOI: 10.1097/prs.0000000000004493
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Microtia Using a Single Expanded Postauricular Flap without Skin Grafting: Experience of 683 Cases

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…Prior epidemiologic research into microtia has been predominantly focused on the condition itself, 1,4547 with little published regarding the demographics of reconstruction specifically. Furthermore, the majority of outcomes research in this arena pertains to aesthetics, 2,23,3540,53,54 thus creating a dearth of information on the overall safety of this operation. This study employed the ACS NSQIP-P database to provide an assessment of nationally reported demographic characteristics and postoperative complication rates of auricular reconstruction for microtia and anotia.…”
Section: Discussionmentioning
confidence: 99%
“…Prior epidemiologic research into microtia has been predominantly focused on the condition itself, 1,4547 with little published regarding the demographics of reconstruction specifically. Furthermore, the majority of outcomes research in this arena pertains to aesthetics, 2,23,3540,53,54 thus creating a dearth of information on the overall safety of this operation. This study employed the ACS NSQIP-P database to provide an assessment of nationally reported demographic characteristics and postoperative complication rates of auricular reconstruction for microtia and anotia.…”
Section: Discussionmentioning
confidence: 99%
“…Under the condition of ensuring sufficient support, a better auriculocephalic sulcus can be achieved. Compared with other single expanded flap reconstruction methods 15,16 using residual ear cartilage to form the tragus, we select the remaining seventh cartilage, which forms the tragus with higher supportability and stronger structure to resistant the skin recession, and has more natural shapes.…”
Section: Discussionmentioning
confidence: 99%
“…Although controversy around tissue expansion exists, a number of surgeons have successfully employed tissue expansion in the reconstruction of congenital microtia and traumatic auricular defects. In China, ear reconstruction surgeons reported thousands of microtia patients were reconstructed by skin expansion techniques (13,14,(19)(20)(21)(23)(24)(25)(26). Usually, the expanded flap is not large enough to drape the entire framework, so skin grafts and postauricular facial flap elevation are consequently inevitable.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the expanded flap is not large enough to drape the entire framework, so skin grafts and postauricular facial flap elevation are consequently inevitable. Xing et al and Li et al described their novel strategies to avoid skin grafts; however, a surgical procedure with ≥3 stages was still required (19,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation